Between Globalism and Isolationism: The Origins of Russia's Arctic Development Strategy. Issue 7 (29th August 2019) - Zubkov, K.I.
ABSTRACT: The article analyzes the early stages of the Russian strategy for Arctic development (in the late nineteenth and early twentieth centuries). In prerevolutionary Russia and the early Soviet Union, the internationalization of Artic development was extremely controversial due to contravening advantages and risks. This encumbered the process of choosing and developing an optimal Arctic strategy and created a contradiction between the interests of Arctic economic development and the interests of national security on the Arctic flank.